A study on the level of awareness on the existence of the counselling services provided by the personnel support program section in human resource management unit of the chief minister's department among the public sector employees housed in Wisma Bapa Malaysia, Petra Jaya, Kuching / Siti Awa Suib - Suib, Siti Awa (2002)
The main objective of the organizations either public sector or private sector is to achieve higher productivity in term of profit or work quality. To achieve this objective, the employees have an important role to ensure that they're organization is active and productive. In order to get the best output from the employees, the organization needs to make sure that their employees are satisfy with their jobs and to their employers so that they will always feel motivated and keep on giving their best in their jobs. When realizing that the discipline cases have increased, the Chief Minister Department have create the Personnel Support Program Section in Human Resource Management Unit in order to help the public sector employees that face problems.